NILAI-NILAI MORAL DALAM CERITA TAPA MALENGGANG SEBAGAI PEMBELAJARAN KARAKTER DI SEKOLAH DASAR - Siti Nurhalizah; Siti Su'adah; Afifah Nur Ismawanti; Yolanda Putri Debi; Gritia Putri Pakpahan; Muhammad Irfan Maulana; Rima Dwi Anggraini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Character education is a crucial aspect of student personality development, particularly in primary schools. This study explores the moral values embedded in the local legend of Tapa Malenggang from Batanghari Regency, Jambi Province, as a potential character learning medium for elementary school students. Using a qualitative research method with interviews, documentation, and literature studies, the research identifies seven key moral values: perseverance, sacrifice, empathy, cooperation, love for nature, ethics and morality, and mental resilience. The study reveals that folk legends can serve as effective educational tools for character formation, offering subtle yet profound moral lessons that help young generations develop integrity and empathy. By analyzing the narrative of Mambang Diawan's journey, the research demonstrates the significance of local cultural heritage in character education and provides insights into innovative approaches for moral learning in the digital era.